Identifikasi Area Pengembangan RTH sebagai Fungsi Ekologis Penyerap Air Hujan di Kecamatan Rungkut Kota Surabaya - Tisa Angelia; Eko Budi Santoso (Jurnal Planoearth, 2019)
Changes in land use have resulted in decreasing green open space as part of green infrastructure. Identification of areas that have potential to develop green open space as rain water absorbers aims to reduce flooding/puddle in Rungkut Distric. The type of research used is quantitative, with overlay analysis techniques. Based on the results of the overlay analysis, there are some areas had the highest weight for developing rainwater absorbent green open space, namely Tulus Harapan Housing (11,7%) and Rungkut Harapan Housing (11,7%). The results of this research were the Kalirungkut Subdistrict as the smallest administrative area that would facilitate goverment policy making related to the development of rainwater absorbing green open space.